2010
DOI: 10.1007/s15010-010-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Borrelia burgdorferi sensu lato from blood of adult patients with borrelial lymphocytoma, Lyme neuroborreliosis, Lyme arthritis and acrodermatitis chronica atrophicans

Abstract: In European patients with Lyme borreliosis, borreliae can be cultured from the blood not only early in the course of the disease but also occasionally later during disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
1
23
1
1
Order By: Relevance
“…All patients with treatment failure had uneventful outcome after retreatment. [18][19][20][21][22][23][24][25] than in adults [26][27][28][29][30][31][32], and 6 reports consisting of ≥20 cases of BL, 2 of which included only children [33,34], 3 included children and adults [2,7,8], and 1 included only adult patients [9]. Our results in 144 consecutive adult patients with BL diagnosed in a single center during a period of 29 years showed that most of the pretreatment clinical characteristics were similar to those in previous reports.…”
Section: Treatment Resultsmentioning
confidence: 99%
“…All patients with treatment failure had uneventful outcome after retreatment. [18][19][20][21][22][23][24][25] than in adults [26][27][28][29][30][31][32], and 6 reports consisting of ≥20 cases of BL, 2 of which included only children [33,34], 3 included children and adults [2,7,8], and 1 included only adult patients [9]. Our results in 144 consecutive adult patients with BL diagnosed in a single center during a period of 29 years showed that most of the pretreatment clinical characteristics were similar to those in previous reports.…”
Section: Treatment Resultsmentioning
confidence: 99%
“…12 Isolation of B. garinii from the blood is reported in 1 of 53 (1.9%) adult patients with BL and concomitant EM. 16 In this study, B. afzelii was isolated in 7% patients with BL younger than 15 years. A 4.5-year-old boy with isolation of B. afzelii from the blood, 1 day before enrolment, noticed a skin lesion at the site of previous tick bite.…”
Section: Discussionmentioning
confidence: 54%
“…and B. miyamotoi [25]. The symptoms of patients suffering from B. miyamotoi infection differ from those described for Lyme borreliosis (e.g., [18]), and no respiratory involvement (as described for some relapsing fever spirochetes; see [34]) has been reported.…”
Section: Introductionmentioning
confidence: 93%